2006
DOI: 10.1001/archinte.166.9.1021
|View full text |Cite
|
Sign up to set email alerts
|

Off-label Prescribing Among Office-Based Physicians

Abstract: Background: Unlike medicines prescribed for Food and Drug Administration-approved indications, off-label uses may lack rigorous scientific scrutiny. Despite concerns about patient safety and costs to the health care system, little is known about the frequency of off-label drug use or the degree of scientific evidence supporting this practice. Methods:We used nationally representative data from the 2001 IMS Health National Disease and Therapeutic Index (NDTI) to define prescribing patterns by diagnosis for 160 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
454
3
25

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 606 publications
(494 citation statements)
references
References 16 publications
12
454
3
25
Order By: Relevance
“…In the United States, one out of five prescriptions regards treatment for an illness for which the drug was not approved (Radley et al, 2006). This study revealed that most off-label uses happen without scientific support.…”
Section: Off-label Indications and Drug Promotional Practicesmentioning
confidence: 95%
“…In the United States, one out of five prescriptions regards treatment for an illness for which the drug was not approved (Radley et al, 2006). This study revealed that most off-label uses happen without scientific support.…”
Section: Off-label Indications and Drug Promotional Practicesmentioning
confidence: 95%
“…According to one study, approximately 21% of all prescriptions are written for off-label indications in office practice, and approximately 73% of those off-label uses have little or no scientific support. 2 In that study, the only drug mentioned that was relatively commonly used in Urology was amoxicillin. Twenty-five percent of amoxicillin usage was offlabel, with half of those prescriptions having 'little or no scientific support'.…”
Section: Introductionmentioning
confidence: 96%
“…[4][5][6] The prescription of psychotropic drugs for management of psychiatric conditions across all age groups is rising worldwide. [7][8][9][10] Evidence showed that some antipsychotics are frequently prescribed as off-label for unapproved indication but only 4% of cases were supported by powerful clinical evidence. 9 Whereas, in India only two studies reported that the prevalence of prescribing off label drugs were 39.5% and 42.34% as per British National Formulary.…”
mentioning
confidence: 99%
“…[7][8][9][10] Evidence showed that some antipsychotics are frequently prescribed as off-label for unapproved indication but only 4% of cases were supported by powerful clinical evidence. 9 Whereas, in India only two studies reported that the prevalence of prescribing off label drugs were 39.5% and 42.34% as per British National Formulary. 11,12 Through extensive literature review it was revealed that till date no such study is conducted in India as per National Formulary of India (NFI).…”
mentioning
confidence: 99%